VIBE SURGA DALAM PERSPEKTIF HADIS - Anas Maulana Abdillah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The modern phenomenon of seeking "vibes" or aesthetic atmospheres on social media reflects a deep yearning for tranquility, yet often results in temporary and illusory satisfaction. This study aims to reconstruct the concept of "heavenly vibes" in Islamic theology as a manifestation of eternal aesthetics using the perspective of Prophet Muhammad’s Hadiths. The research employs a qualitative method with a contemporary thematic Hadith (maudu’i) approach and Grounded Theory. Data collection was conducted through digital tracing of authoritative Hadith compendiums, subsequently analyzed through open, axial, and selective coding of 21 selected Hadith samples. The results map "heavenly vibes" into three primary clusters: futuristic architecture and landscapes made of precious minerals, a sensory atmosphere that indulges all senses, and a social order based on spiritual meritocracy. The analysis reveals that Paradise is not merely an abstract metaphor but a tangible ecosystem where time functions progressively and appreciatively, as evidenced by the "Heavenly Market" phenomenon that enhances the physical aesthetics of its inhabitants and an inclusive rehabilitation mechanism for sinners. The discussion concludes that the culmination of this atmosphere is the Beatific Vision, or beholding the Face of Allah, which perfects the entire sensory experience. This study implies a paradigm shift in understanding eschatology from mere dogma to a motivational narrative of beauty relevant to the aesthetic standards of the millennial generation.